Formation of SS316L Single Tracks in Micro Selective Laser Melting: Surface, Geometry, and Defects - Zhiheng Hu; Balasubramanian Nagarajan; Xu Song; Rui Huang; Wei Zhai; Jun Wei (Advances in Materials Science and Engineering)
To fabricate complex parts with a fine resolution and smooth finish, micro selective laser melting (SLM) has been developed recently by combining three attributes: small laser beam spot, fine powder size, and thin layer thickness. This paper studies the effect of the micro-SLM process parameters on the single track formation of 316L stainless steel. The surface morphology, geometrical features, and defects have been analyzed in detail. The results highlight that laser power and scanning velocity have a significant effect on the formation of single tracks. The single tracks fabricated through micro-SLM with varying process parameters are classified into four types: no melting, discontinuous, continuous but unstable, and continuous tracks. Besides, the top surface of the tracks is observed with “double-crest” morphology, due to the high recoil pressure gradient generated by the extremely fine spot size. In addition, molten pool geometry (width, depth, and height) has been characterized to study the mode of the molten pool in micro-SLM. Finally, the occurrence of two typical defects within the tracks, keyhole pore and cavity at the edges, has been studied.